Research On The Correlation Between Mathematics And Physics Of The Senior High School Students - Chen, Jihe; Zhao, Qiulian; Huang, Yuxian (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2021)
Materialist dialectics holds that the material world is generally connected, and the realization of the calculation, verification and other goals involved in physics requires the use of mathematical knowledge as the research tool and language, and the use of mathematical methods and mathematical ideas for reasoning and analysis, which shows that there is a close relationship between mathematics and Physics. Analyzing the influence of mathematics on physics from the perspective of data is helpful for teachers to improve the teaching process of physics, promote students' ability of mathematics application and physics learning, and improve the quality of high school teaching. In this paper, through statistical analysis and questionnaire research. The scores of mathematics and physics in a school were collected and analyzed by SPSS22.0 software. It is found that mathematics achievement has a significant influence on physics achievement. Then through the questionnaire survey of whether mathematics has an impact on physics, we get a positive answer from the perspective of students. The final conclusions are as follows: (1) there is a positive correlation between mathematics achievement and physics achievement; (2) more than half of the students can use mathematical methods to solve problems when learning physics; (3) most students hope that teachers can teach them how to use mathematical methods in physics learning. Through these conclusions, we can know that mathematics achievement has a very important impact on physics achievement. It reminds us that we should pay attention to students' mathematics education.